Public Service Planning in the New Public Service Perspective (Study at the Nganjuk District Population and Civil Registration Office) - Arie Kumala Nisa'; Soesilo Zauhar; Hermawan Hermawan (Wacana Journal of Social and Humanity Studies, 2019)
Service planning is needed as a guideline to achieve service goals. The contribution of bureaucrats in agencies and communities as service owners is needed in planning public services to find out public needs. The involvement of bureaucrats and citizens for the public interest is the principle of the New Public Service. However, this plan has been dominated by a top-down approach and inefficient implementation of public services. This research aims to analyze in the New Public Service perspective. This research method is descriptive qualitative research by describing service conditions, planning processes and analyzing the planning in the New Public Service perspective. The results of this study are that in the planning process, other bureaucrats in the agency were not involved, coordination and communication between employees was weak. Then the activities carried out in the implementation of the plan are socialization and shuttle service as an effort to provide equal service. However, infrastructure and human resources are inadequate so that services are inefficient and targets are not achieved. The recommendation of this study is that public service planning requires the application of the principles of the New Public Service so that the government knows what the public needs are. thus the public services provided can satisfy citizens in accordance with the values in the New Public Service.Keywords: Planning, Public Service, New Public Service